2017
DOI: 10.1016/j.jstrokecerebrovasdis.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Resistive Training and Molecular Regulators of Vascular-Metabolic Risk in Chronic Stroke

Abstract: Background Proliferator activator receptor (PPAR)-γ coactivator (PGC-1α) gene and Sirtuin-1 (SIRT1) respond to physiological stimuli and regulate insulin resistance. Inflammatory markers TNF-α, interleukin-6, C-reactive protein (CRP) and the soluble forms of intracellular adhesion molecule (sICAM-1) and vascular CAM-1 (sVCAM-1) are associated with increased risk of diabetes and coronary heart disease. Resistive training reduces hyperinsulinemia and improves insulin action in chronic stroke. Yet, the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Three single-group studies that included RT interventions alone (n = 10 to 18 participants) did not result in a change in total body lean mass likely owing to an insufficient total body stimulus (2 sets of 3 lower-extremity exercises). 57-59 Furthermore, an earlier study conducted by our group failed to demonstrate a significant increase in total body lean mass by DXA in 41 poststroke participants after 6 months of AT+RT. 47 Similar to the current study, the RT program targeted all major muscle groups (1 to 2 sets of 10 to 11 exercises) and was progressed by a combination of increasing repetitions and weight load.…”
Section: Discussionmentioning
confidence: 81%
“…Three single-group studies that included RT interventions alone (n = 10 to 18 participants) did not result in a change in total body lean mass likely owing to an insufficient total body stimulus (2 sets of 3 lower-extremity exercises). 57-59 Furthermore, an earlier study conducted by our group failed to demonstrate a significant increase in total body lean mass by DXA in 41 poststroke participants after 6 months of AT+RT. 47 Similar to the current study, the RT program targeted all major muscle groups (1 to 2 sets of 10 to 11 exercises) and was progressed by a combination of increasing repetitions and weight load.…”
Section: Discussionmentioning
confidence: 81%
“…No participants experienced any adverse events in the included RCTs. 100.0 % 119 117 Total (95 % CI) Heterogeneity: Tau 2 = 0.00; Chi 2 = 0.74, df = 3 (P = 0.86); I 2 = 0 % Test for overall effect: Z = 3.65 (P = 0.0003) 100.0 % 88 85 Total (95 % CI) Heterogeneity: Tau 2 = 0.00; Chi 2 = 0.83, df = 2 (P = 0.66); I 2 = 0 % Test for overall effect: Z = 2.60 (P = 0.009) Community-based exercise therapy was reported to be a feasible method of modifying metabolic risk factors [29,30]. A 23 % increase (0.3 mmol/L) of high-density lipoprotein cholesterol (HDL-C) was revealed after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the patterns of exercise are very important for the generation of irisin. The forms of exercise include endurance and resistance exercise training; the former is an aerobic and cardiovascular form of exercise, while the latter focuses more on muscle strength and hypertrophy (Cornelissen and Smart, 2013 ; Ryan et al, 2017 ). At present, evidence suggests that irisin is involved in endurance exercise.…”
Section: The Role Of Irisin In Strokementioning
confidence: 99%
“…Physical exercise can reportedly alleviate some of these pathophysiological processes. In addition, in the rehabilitation stage of stroke, exercise can also effectively improve sequelae symptoms (Li et al, 2017 ; Ryan et al, 2017 ). In 2013, studies reported that brain-derived neurotrophic factor (BDNF) is a possible mediator of the neurological benefits of exercise (Mang et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%